Synchronization of Protein and Energy Supply in the Rumen to Improve Low Quality Feed Efficiency - Anggraeny, Yenny Nur; Soetanto, H; ., Kusmartono; ., Hartutik (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Agricultural by-products which can be used as source of roughage, have some limitations as they contain low crude protein and low dissolved organic material and high crude fiber. Synchronization of nutrients through supplementation can provide a positive effect on microbial protein synthesis, especially on ruminants fed low quality forage. Contribution of protein from rumen microbes is essential for feed management based on agricultural by product. Microbial protein can supply 70-100% of the total protein available for ruminants fed low quality feed. Microbial protein has amino acid profile which is ideal to meet ruminantâs requirement. This paper describes synchronization of protein and energy supply in the rument that has been applied by several countries. Application of this synchronization in Indonesia is still limited on: (1) Arranging the use of feedstuffs through the ratio of forage and concentrate; (2) Supplementation of protein and energy sources; and 3) Feeding frequency regulation. The application of synchronization through the use of feed ingredients based on degradation level and its index value is still limited due to lack of data on protein and energy degradation of feed ingredients used in Indonesia. Therefore, the information on the degradation value of protein and energy of feed ingredients in Indonesia is necessary in order to optimize the use of low quality feed ingredients. Key words: Nutrient synchronization, microbial protein, fiber source, agricultural by-product